LANGUAGE STYLE IN THE LYRICS OF THE PINK ALBUM SONGS BY LUKAS GRAHAM - Sembiring, Rifky Sultan Nico; Tambusai, Azhary (Fakultas Sastra UMN AL Washliyah, 2025)
This research analyzes the language styles in the lyrics of Lukas Graham’s Pink album using Gorys Keraf’s theory, focusing on two classifications language styles based on sentence structure and meaning with the aim of identifying the types used and interpreting their meanings, employing a qualitative descriptive method, the researcher examined 11 song lyrics through domain analysis, revealing that repetition (especially epizeuxis and anaphora) is the most dominant structure-based style, while meaning based styles include symbolism, metaphor, personification, hyperbole, irony, paradox, antithesis, euphemism and rhetorical question, where denotative meaning appears more frequently than connotative meaning, ultimately showing that Lukas Graham’s use of language styles enhances emotional expression, clarity, and artistic quality in the lyrics.